# Which of the following shows 9x^{2}y - 4x + 3y^{3}x - 2y^{2} written in standard form.

9x^{2}y - 4x + 3y^{3}x - 2y^{2}

3y^{3}x - 2y^{2} + 9x^{2}y - 4x

9x^{2}y - 4x - 2y^{2} + 3y^{3}x

3y^{3}x + 9x^{2}y - 2y^{2} - 4x

**Solution:**

Given, the expression is 9x^{2}y - 4x + 3y^{3}x - 2y^{2}

We have to write this expression in a standard form.

We can arrange each term as the reducing degree of each term.

Degree of 9x^{2}y = degree of x + degree of y

= 2 + 1

= 3

Degree of 4x = 1

Degree of 3y^{3}x = degree of x + degree of y

= 1 + 3

= 4

Degree of 2y^{2} = 2

Now arrange the expression in descending order of degree,

3y^{3}x + 9x^{2}y - 2y^{2} - 4x

Therefore, the expression in standard form is 3y^{3}x + 9x^{2}y - 2y^{2} - 4x.

## Which of the following shows 9x^{2}y - 4x + 3y^{3}x - 2y^{2} written in standard form.

**Summary:**

The expression 9x^{2}y - 4x + 3y^{3}x - 2y^{2} written in standard form is 3y^{3}x + 9x^{2}y - 2y^{2} - 4x.

Math worksheets and

visual curriculum

visual curriculum